Autoimmune disease of head and neck, imaging, and clinical review. Issue 5 (October 2022) - Paydar, Alireza; Jenner, Zachary B; Simkins, Tyrell J; Chang, Yu-Ming; Hacein-Bey, Lotfi; Ozturk, Arzu; Birkeland, Andrew; Assadsangabi, Reza; Raslan, Osama; Shadmani, Ghazal; Apperson, Michelle; Ivanovic, Vladimir
Autoimmune disease of the head and neck (H&N) could be primary or secondary to systemic diseases, medications, or malignancies. Immune-mediated diseases of the H&N are not common in daily practice of radiologists; the diagnosis is frequently delayed because of the non-specific initial presentation and lack of familiarity with some of the specific imaging and clinical features. In this review, we aim to provide a practical diagnostic approach based on the specific radiological findings for each disease. We hope that our review will help radiologists expand their understanding of the spectrum of the discussed disease entities, help them narrow the differential diagnosis, and avoid unnecessary tissue biopsy when appropriate based on the specific clinical scenarios.